Proposta de melhoria no processo de atendimento em uma farmácia de dispensação de psicotrópicos: uma aplicação do LEAN e ferramenta FMEA - Paiva, Livia Valerya da Cruz (2021)
The logistic services related to medications have high demand, with fractionated processes and several professionals involved, performing sequential activities as in a manufacturing production line. Failures in these processes imply costs to health systems and risks to patients. The delineation of flows and application of quality tools provide opportunities for process improvement, optimizing time, human and financial resources, besides offering more security in the correct dispensing and rational use of medicines. Objectives: To describe the stages of dispensing psychotropic drugs in a public pharmacy with the suggestion of a new flow that improves the efficiency of the service process, using the fundamentals of Lean Manufacturing and the FMEA-HC (Healthcare Failure Mode and Effect Analysis) tool. Methods: The study was descriptive and used the Lean Manufacturing method in the process of dispensing psychotropic drugs in a pharmacy in the municipality of Caucaia. A design of the current flow was made using the LucidChart tool to identify the steps that did not add value to the process and propose a new flow in order to organize and streamline the process. Two quality indicators were used (total process time and number of corrections of the Patient Care Form) to enable comparison between the current flow and the new proposed flow. The study of potential failures was added, with the use of the FMEA-HC tool in addition to the new flow. Results: After mapping the current flow at the study site, it was possible to get acquainted with the medication dispensing process, visualizing excess and critical points that did not add value to the process and doing rework, such as repetitive checking of documents and wrong separation of medications. A new flow was designed with the reformulation of the steps to reduce the waiting time of patients by repositioning the pharmacist and administrative agents. In this approach, the FMEA-HC tool was used, listing the potential failures that could interfere with the service and the recommended actions for each situation, in case they occur. Conclusion: The implementation of the new service flow, by removing all unnecessary steps, provided the creation of a leaner flow and less exposure to failures, improving the efficiency of the process, optimizing and reducing the time of attendance, and increasing the safety and efficiency of activities. In addition, this new service flow minimizes stress, generating a higher quality service and promoting better satisfaction for patients and professionals who make up the pharmacy staff.